Graphene encapsulated porous monodisperse MnO microspheres as high-performance anode material for lithium storage. Issue 10 (July 2019) - Cheng, Fangyan; Chen, Yujie; Sun, Antao; Zhou, Xiangyang; Yang, Juan; Tang, Jingjing
Abstract: Graphene encapsulated porous monodisperse MnO microspheres (MnO@rGO) are synthesized by a feasible in-situ precipitation of MnCO3 on graphene oxide and followed by an annealing process. When serving as an anode for Li-ion batteries, the MnO@rGO electrode exhibits a reversible specific capacity of 718 mAh g −1 at 0.5 A g −1 after 300 cycles and good rate capability. The porous structure of MnO and its encapsulation by highly conductive graphene attribute to its superior electrochemical performance.